Implementation of the Concept of the Harmonious Family of the Tarjih Council for Muhammadiyah Residents in Kuala Lumpur, Malaysia - Mushlih Candrakusuma; Wawan Kusnawan; Rizki Listyono Putro (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to examine the implementation of the concept of the Sakinah Family as formulated by the Muhammadiyah Tarjih Council in the Muhammadiyah community in Kuala Lumpur, Malaysia. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation of 45 informants from various family backgrounds. The results of the study indicate that the theoretical understanding of Muhammadiyah residents of the concept of the Sakinah Family is still limited, with only 11% of informants formally familiar with the concept. However, their family life practices reflect values ​​that are in line with the principles of the Sakinah Family, such as reading the Qur'an together, regular Islamic studies, and choosing monogamy as the ideal form of family. The main challenges in implementing this concept include low conceptual literacy in the perspective of Tarjih Muhammadiyah and adaptation to different local cultures. This study recommends strengthening conceptual education through community-based programs such as seminars, learning modules, and academic discussions to improve understanding and application of the Sakinah Family concept in a global context.